Graph theory and additive combinatorics : exploring structure and randomness - Zhao, Yufei (Cambridge: Cambridge University Press, 2023)
"This graduate level textbook covers classical and modern developments in graph theory and additive combinatorics, presenting arguments as a cohesive whole. Students will appreciate the chapter summaries, many figures and exercises, as well as the complementary set of lecture videos freely available through MIT OpenCourseWare"--
Appetizer : triangles and equations -- Forbidding a subgraph -- Graph regularity method -- Pseudorandom graphs -- Graph limits -- Graph homomorphism inequalities -- Forbidding 3-term arithmetic progressions -- Structure of set addition -- Sum-product problem -- Progressions in sparse pseudorandom sets.
Includes bibliographical references and index.
Keywords: Graph theory; Additive combinatorics